2015
DOI: 10.1177/1473325015589803
|View full text |Cite
|
Sign up to set email alerts
|

Nominal Group Technique: An accessible and interactive method for conceptualizing the sexual self-advocacy of adults with intellectual and developmental disabilities

Abstract: People with intellectual and developmental disabilities must often advocate for themselves in many facets of life, including sexuality. Because of this, sexual self-advocacy is an important concept to develop and apply to policy and practice. This paper provides a conceptualization of sexual self-advocacy, a view of sexuality formulated by adults with intellectual and developmental disabilities that is closely tied to the values of the SelfAdvocacy Movement. In describing the study process, this paper also put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…The approach taken to ranking topics in this project verified that the similarity to real-world discussions and conversations found in the NGT does indeed provide an accessible method of participation for those with cognitive disabilities (Owen et al, 2016). However, it also revealed that it does so for those with other impairments too.…”
Section: Steps 1 and 2: Individual Generation Of Ideas And Round-robisupporting
confidence: 57%
See 2 more Smart Citations
“…The approach taken to ranking topics in this project verified that the similarity to real-world discussions and conversations found in the NGT does indeed provide an accessible method of participation for those with cognitive disabilities (Owen et al, 2016). However, it also revealed that it does so for those with other impairments too.…”
Section: Steps 1 and 2: Individual Generation Of Ideas And Round-robisupporting
confidence: 57%
“…More recently, one of the areas where the NGTs' flexibility has proven to be of great value is as an accessible group research method involving people with cognitive disabilities. This included those with mild IDs (Bekkema, de Veer, Hertogh, & Francke, 2016;Roeden, Maaskant, & Curfs, 2011), those with ID and developmental disability (Friedman, Arnold, Owen, & Sandmanet, 2014;Owen et al, 2016), and those with aphasia (Garcia, Barrette, & Laroche, 2000;Hinckley, Boyle, Lombard, & Bartels-Tobin, 2014;Wallace et al, 2017). Although, "to date, NGTs have only been employed for people with ID and aphasia, a fraction of the spectrum of disabilities," and "more research is required to develop a greater understanding of additional NGT method considerations for other disabilities" (Lakhani, Watling, Zeeman, Wright, & Bishara, 2018, p. 2113 The project cited in this article sought to fill this void.…”
Section: Previous and Recent Applications Of The Ngtmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the eight included studies, the majority (n = 6; 75%) were published in the previous two years The purpose of each NGT varied across the included studies. For studies including people with ID, the research questions focused on sexual self-advocacy [28,29], relationships with carers [19], end of life care [18,25], and participants' evaluation of healthcare tools available to them. [30] For studies including people with aphasia, the research questions centred on participants' impressions of the future of research in aphasia [27], perceptions of barriers to work reintegration [26], and what healthcare domains (e.g., communication; participation) were important to them.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The facilitated discussions and voting process of the NGT minimised typical power dynamics of diverse stakeholder groups and allowed varied stakeholders to contribute equally to group discussions [48]. Five key advantages of NGT include (1) discouraging idea domination by more vocal or powerful members of the group [49], (2) group members' satisfaction as it requires little preparation and allows for immediate dissemination of results [50], 3limiting possible researchers' biases as data are interpreted by participants [51,52], (4) giving participants a sense of achievement as, by using this method, participants are more likely to reach clear outcomes [45], and (5) a money-, time-and resource-efficient technique as it generates a sizable amount of information within a short time frame using little resources in a single occasion [43,48]. We employed an adapted version of the NGT that entails five steps (see Additional file 1 for a detailed description of each step taken during our first event), as follows: (1) silent generation, (2) round robin engagement, (3) clarification, (4) categorisation and (5) ranking [50].…”
Section: Optimisation Of Stakeholder Partnership Strategiesmentioning
confidence: 99%